In Situ Extraction And Transesterification Of Jatropha Curcas L. Seeds Using Supercritical Fluids For The Synthesis Of Biodiesel - Steven, Lim (2013)
Jatropha curcas L. (JCL) is an emerging non-edible oil plant which has a high potential as the feedstock for biodiesel production. In this study, supercritical in situ extraction and transesterification process (SET) developed from process intensification was applied together with methanol for the production of biodiesel from JCL in a high pressure batch reactor. Raw material characterizations were performed on the JCL oil seeds in this study to determine their physical and chemical properties. Pre-treatments of the solid seeds including solid particle size (0.5-2.0 mm), de-shelling and heat treatment at five different temperatures (45°C-105°C) and two different durations (12h and 24h) were also investigated. It was discovered that de-shelling of JCL seeds had highest influence on the product yield, followed by sieving and heat treatment. SET process was conducted in the process temperature range of 240°C to 320°C, process pressure of 4.0 MPa to 24.0 MPa, methanol to solid seeds ratio (SSR) of 2.5 ml/g to 15.0 ml/g, space loading of 90.0 ml/g to 18.0 ml/g, n-hexane to solid seeds ratio of 0 ml/g to 6.0 ml/g, process holding time of 0 min to 35 min and stirring speed of 0 rpm to 500 rpm. Co-solvents which were being employed in the process to reduce the process severity were n-pentane, n-heptane, tetrahydrofuran (THF), toluene, nitrogen gas (N2) and carbon dioxide gas (CO2). Their amounts were varied from 1.0 ml/g to 5.0 ml/g for liquid and 10 bar to 50 bar for gases. It was found that n-pentane and CO2 could further reduce the optimum operating temperature and amount of methanol for SET process due to promoting higher miscibility between reactants.